The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s10529-022-03284-5
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenes is a solvent tolerant organism secreting a solvent stable lipase: potential biotechnological applications

Abstract: Purpose The emerging biobased economy will require robust, adaptable, organisms for the production and processing of biomaterials as well as for bioremediation. Recently, the search for solvent tolerant organisms and solvent tolerant enzymes has intensified. Resilient organisms secreting solvent stable lipases are of particular interest for biotechnological applications. Methods Screening of soil samples for lipase-producing organisms was carried out on Rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…Our findings corroborate a previous study that reported haemolytic activity and lipase-producing (Al-Mashhadany, 2019). has been reported to retain approximately 80% lipase activity upon incubation for 24 h in 30% (v/v) methanol (Priyanka ., 2022). Olaniran .…”
Section: Monocytogenes Et Al L Monocytogenessupporting
confidence: 93%
“…Our findings corroborate a previous study that reported haemolytic activity and lipase-producing (Al-Mashhadany, 2019). has been reported to retain approximately 80% lipase activity upon incubation for 24 h in 30% (v/v) methanol (Priyanka ., 2022). Olaniran .…”
Section: Monocytogenes Et Al L Monocytogenessupporting
confidence: 93%
“…In order to obtain higher commercial value, the search for highly tolerant lipases with organic solvents has never stopped. Priyanka et al [ 100 ] screened a solvent-tolerant Listeria monocytogenes that secretes a solvent-tolerant lipase that loses only 20% of its activity after 24 h in a 30% volume of methanol. Yasir Ali et al [ 101 ] isolated a new strain of Pseudomonas spp.…”
Section: Overview Of the Biological Catalyst: Lipasementioning
confidence: 99%